Proceedings of the Society for Experimental Biology and Medicine : vol. 41 - Society for Experimental Biology and Medicine (New York, N.Y.) (New York : Blackwell Science, 1939)
Proceedings of various branches of the society are included.
List of members in each volume.
Includes index.
Life sciences collection
Excerpta medica
PESTDOC
RINGDOC
VETDOC
Keywords: Physiology -- Periodicals; Medicine, Experimental -- Periodicals; Biology -- Periodicals; Medicine -- Periodicals